Health-promoting effects of bioactive compounds in blackcurrant (Ribes nigrum L.) Berries - Michał Oczkowski (National Institute of Public Health - National Institute of Hygiene, 2021)
Blackcurrant (BC) is a well-known and appreciated berry fruit in our country and Poland is the largest BC producer among European Union countries and the second, after Russia, producer in the world. Due to the short shelf life of BC, its consumption in fresh form is relatively low , therefore the berries are processed into juices, jams, jellies, and freeze-dried products or alcoholic beverages. The high nutritional value of BC berries result from high content of bioactive compounds (among others, vitamin C, anthocyanins, pectins, organic acids, as well as polyunsaturated fatty acids contained in seeds of the fruit). Anthocyanins (ANTs) create the largest group among all polyphenolic compounds contained in BC. The results from different studies confirm that ANTs are important in attenuation oxidative stress parameters in the organism, and therefore can reduce the risk of certain non-communicable chronic diseases. Consumption of unprocessed and processed blackcurrants (i.e. juices and products containing fruit extracts) may support the nutrition therapy of cardiovascular diseases, certain eye diseases and may normalize the lipid profile of the blood plasma. Additionally, the beneficial profile of unsaturated fatty acids from BC seeds supports the therapy of autoimmune diseases. This article is attempts to summarize the results of the studies on the anti-inflammatory, immunomodulatory, anti-tumor and antimicrobial effects of BC bioactive compounds including the mechanisms of their action depending on the form of the fruit (e.g. juice, whole fruit extract, dried pomace, or seed oil). The article also highlights the potential use of BC in production of functional food, important in the dietary prevention of non-communicable chronic diseases resulting from increased oxidative stress in the organism.